Electronic document management system - Patah Akhir, Emelia Akashah; R., Syamsul Rizal; Jusoff, Kamaruzaman; E., Christon (IDOSI Publications, 2011)
Electronic Document Management System (EDMS) is needed by many organizations to properly managed large volumes of physical documents. One of them is Supply Chain Management (SCM) department of Oil and Gas (O&G) company in Malaysia. The objective of this research is to develop a framework of EDMS that is tailor-made to the SCM department, which is believed could help the department to manage their physical documents which are now located in their rented external storage due to the lack of space in the department itself. The requirements gathering is conducted by using interview method. The current business flow which involved the usage of the documents from one unit to another needed to be fully understood before developing the EDMS framework. This research has successfully developed an EDMS framework of SCM department and it could be used in developing the EDMS for future research.